Envolvimento dos receptores trpv1, trpa1, trpm8 e nmda no efeito antinociceptivo do derivado diterpênico semissintético sm-2 em zebrafish adulto - Basílio, Sarah Rodrigues (2024)
Orofacial pain is a prevalent clinical condition in the population with an impact on patients quality of life. The management of orofacial pain may involve both non-pharmacological and pharmacological approaches. However, it is important to highlight that drug therapies may entail substantial risks and side effects, making it essential to search for new pharmacological therapeutic alternatives. In previous studies, the extract of Stemodia maritima L., the diterpene stemodin and its semisynthetic derivative SM-2 showed antinociceptive and anti-inflammatory effects in the treatment of acute temporomandibular joint (TMJ) pain, although the underlying mechanism of action of SM-2 remains to be elucidated. Therefore, the aim of this study was to evaluate the motor, orofacial antinociceptive and anxiolytic effects of SM-2 in adult zebrafish and to investigate its mechanism of action through TRPV1, TRPA1, TRPM8 and NMDA receptors. For this purpose, adult zebrafish, with n = 8/group, treated with SM-2 at doses of 0.01 or 0.1 µg/mL were used. The motor activity of zebrafish was evaluated by means of the open field test. Then, acute orofacial nociception was induced by capsaicin (TRPV1 agonist), cinnamaldehyde (TRPA1 agonist), menthol (TRPM8 agonist) or glutamate (NMDA agonist). In another sequence of experiments, the animals were pretreated with capsazepine (TRP V1 antagonist), HC-030031 (TRPA1 antagonist), AMTB (TRPM8 antagonist) or ketamine (NMDA antagonist) in order to investigate the mechanism of action of SM-2. Furthermore, the anxiolytic activity of SM-2 was also evaluated by means of the light-dark test. SM-2 did not alter the locomotor behavior of the animals and SM-2 reduced orofacial nociception caused by TRPV1, TRPA1, TRPM8 and NMDA receptor agonists. Pretreatment with HC-030031, AMTB or ketamine did not alter the antinociceptive effect of SM-2, however, administration of capsazepine prevented the effect of SM-2. Treatment with SM-2 promoted a longer stay of the animals in the light zone of the aquarium, indicating the anxiolytic potential of SM-2. Based on these findings, we can suggest that SM-2 has an antinociceptive action mediated by the TRPV1 receptor, in addition to an anxiolytic-like effect.